1977
DOI: 10.1080/00221325.1977.10533226
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Sons' Feelings of Being Understood by Their Fathers and Measures of the Sons' Psychological Functioning

Abstract: Factor analysis of a questionnaire designed to measure a son's feeling of being understood by his father is reported. The questionnaire, which contained 12 paragraphs each purporting to be an aspect of the son's feeling of being understood by his father, was administered in small groups to a sample of 413 male college students along with three indices of son's level of general functioning--a self-concept scale, a somatic complaints inventory, and the degree of help-seeking behavior. Five interpretable factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Because earlier research associates gender identity with role‐modeling by the same‐sex parent (Huttenen, 1992; Lamb, 2000; Lamb & Tamis‐Lemonda, 1997; Millen & Roll, 1997), it is no wonder that so little focus is placed on the father–daughter relationship and how father involvement matters equally to girls as it does to boys. According to Lamb and Tamis‐Lemonda (1997), “Boys seemed to conform to the sex‐role standards of their culture when their fathers were warm, regardless of how masculine the fathers were” (p. 5).…”
Section: Context Of Gender Roles and Female Developmentmentioning
confidence: 99%
“…Because earlier research associates gender identity with role‐modeling by the same‐sex parent (Huttenen, 1992; Lamb, 2000; Lamb & Tamis‐Lemonda, 1997; Millen & Roll, 1997), it is no wonder that so little focus is placed on the father–daughter relationship and how father involvement matters equally to girls as it does to boys. According to Lamb and Tamis‐Lemonda (1997), “Boys seemed to conform to the sex‐role standards of their culture when their fathers were warm, regardless of how masculine the fathers were” (p. 5).…”
Section: Context Of Gender Roles and Female Developmentmentioning
confidence: 99%
“…Many studies looking exclusively at the influence of variations in father love deal with two topics: (a) gender role development (Fish & Biller, 1973; Green, 1982; Huttenen, 1992; Millen & Roll, 1997; Musser & Fleck, 1983) and (b) father involvement (Amato & Rivera, 1999; Biller, 1993; K. N. Harris, Furstenberg, & Marmer, 1998; Radin, 1981). Studies of gender role development emerged prominently in the 1940s and continued through the 1970s (Lamb, 1997, 2000).…”
Section: Six Categories Of Studies Show the Influence Of Father Lovementioning
confidence: 99%
“…Researchers have examined the important role of fathers in male development for decades (Harper & Fine, 2006; Maton, Hrabowski, & Greif, 1998; Millen & Roll, 1977). The quality of the father–child relationship positively affects the child’s overall well-being (Harper & Fine, 2006).…”
mentioning
confidence: 99%
“…The quality of the father–child relationship positively affects the child’s overall well-being (Harper & Fine, 2006). Researchers reported that the presence of a residential, biological father or an actively present nonresidential, biological father can (a) inhibit violence in adult men (Mackey & Mackey, 2003), (b) lead to better psychological functioning (Dubowitz et al, 2001; Millen & Roll, 1977), and (c) have a profound influence on academic and professional achievement (Hebert, Pagnani, & Hammond, 2009; Maton et al, 1998). The presence of a father who demonstrates love, support, guidance, and is a positive role model is an invaluable contributor to healthy development in young Black males (Hebert et al, 2009; Morman & Floyd, 2006).…”
mentioning
confidence: 99%